Composición de cuatro obras musicales basadas en la innovación sonora y tecnológica del género tradicional ecuatoriano Chaspishka - Guamán Sarango, Jheyson Alexander (2024)
Traditional music is transmitted from generation to generation, through orality, as is the case with the Chaspishka, a traditional rhythm that has been adapted over time. Based on this statement, it has been proposed to make a composition of four musical pieces in the traditional genre representative of the Kichwa Saraguro people such as the Chaspishka, highlighting its sound innovation and its technological development, considering that this rhythm has been adapted to their social reality and innovated from its origin to the present. The objective of this artistic product derived from the Curricular Integration Work is to contribute to the strengthening of the cultural identity of the Kichwa Saraguro people, through the composition of four musical works based on the traditional autochthonous Chaspishka genre. This will allow us to know not only the musical genre as such, but also the link it has with the community, its culture, and its evolution over time. With this porpuse, the search for theoretical sources that support the artistic product has been carried out, as well as the use of methodological tools that started from the sound and technological investigation of the Chaspishka rhythm and in this way have the necessary musical knowledge to carry out the compositional process. The results of this research led to the composition of four musical works, which not only contribute to cultural identity, but also contribute to the dissemination of this traditional rhythm. Finally, some conclusions and recommendations are proposed that promote further deepening on these types of autochthonous rhythms and also urging that new musical creative processes be carried out based on this type of traditional Ecuadorian genres. Keywords: Cultural identity, composition, innovation, dissemination, chaspishka, Saraguro.